An Analytical Approach to Teaching Arabic Literature through Deixis and Forensic Linguistics - Afifah, Nur; Muhammad Reko (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Deixis plays a central role in establishing reference and meaning in narrative discourse, particularly in literary texts that rely on dialogue and shifting perspectives. Despite its analytical potential, deixis has received limited attention within forensic linguistics–oriented literary studies, especially in Arabic short fiction. This study addresses this gap by applying deixis analysis to uncover referential and symbolic clues in the short story Qatilu Qadim by Naguib Mahfouz, with the aim of identifying the murderer of the character Qahiri. Employing a descriptive qualitative approach, the study uses observation and systematic note-taking based on Stephen C. Levinson’s theory of deixis, integrated with principles of forensic linguistics. Deictic expressions related to person, time, space, and social relations are analyzed to trace patterns of proximity, access, and control within the narrative. Legal interpretation of the crime is discussed in relation to the sociocultural and legal context relevant to the author. The findings reveal that Qahiri’s murderer is Abduh Mawahib, his servant, who maintained continuous physical and social proximity to the victim during a period of isolation from relatives and colleagues. This study demonstrates the effectiveness of deixis analysis as a forensic linguistic tool in literary investigation and highlights its pedagogical value in Arabic language education by fostering critical reading and analytical reasoning.